Quality Improvement Summit 2016: Shared Decision Making and Prostate Cancer Screening. Issue 6 (November 2018) - Makarov, Danil V.; Holmes‐Rovner, Margaret; Rovner, David R.; Averch, Timothy; Barry, Michael J.; Chrouser, Kristin; Gee, William F.; Goodrich, Kate; Haynes, Mike; Krahn, Murray; Saigal, Christopher; Sox, Harold C.; et al.
Abstract : Introduction: : The American Urological Association Quality Improvement Summit occurs regularly to provide education and promote dialogue around the issues of quality improvement and patient safety. Nearly all prostate cancer screening guidelines recommend shared decision making strategies when determining whether prostate specific antigen testing is right for a specific patient. This summit, held in partnership with the Society for Medical Decision Making, focused on techniques to identify and understand patient values in relation to prostate cancer screening and treatment, and to promote incorporation of shared decision making into prostate cancer screening discussions. Methods: : Information presented at the Quality Improvement Summit was provided by physicians and leading experts in the field of shared decision making. The open forum of this summit encouraged contributions from participants about their personal experiences with shared decision making and their thoughts on the tools presented during the day. Results: : Shared decision making supports collaboration between physician and patient in situations where there are multiple preference sensitive options. Conclusions: : Practitioners should include formal shared decision making procedures surrounding prostate specific antigen testing in their practices to ensure that testing is in accordance with patient values and desired outcomes. Tools and strategies like those reviewed in this Quality Improvement Summit are invaluable for alleviating potential burden on providers, ensuring communication and improving quality of care.